Evaluation of continence following 532 nm laser prostatectomy for patients previously treated with radiation therapy or brachytherapy. Issue 6 (27th June 2013) - No, David; Osterberg, E. Charles; Otto, Brandon; Naftali, Izolda; Choi, Benjamin
Abstract Introduction/Objective Urinary complications such as bladder outlet obstruction or urinary retention following radiation therapy or brachytherapy have been reported in up to 15% of men. When conservative therapy has failed, surgical intervention with transurethral resection of the prostate (TURP) may be performed, but carries a significant risk of incontinence, ranging from 18% to 70% in reported literature. We reviewed a cohort of men previously treated with radiation or brachytherapy, who underwent laser prostatectomy. Methods From February 2004 to October 2011, 12 patients (Six = brachytherapy and Six = external beam radiation) underwent 532 nm GreenLight™ laser prostatectomy by a single surgeon (BBC) for chronic retention or debilitating obstructive symptoms. Preoperative, intraoperative, and postoperative parameters were collected prospectively and reviewed retrospectively. Statistical analysis was performed with a Wilcox Rank sum test with significance defined as P < 0.05. Results The median patient age was 77.4 (Interquartile range (IQR) 73.9, 79.1). Prior to surgery, five patients were catheter dependent. Intraopertively, the median operative time was 48 minutes (IQR 35, 67); median lasing time was 28 minutes (IQR 23, 44); median Joules used was 126, 873 (IQR 95, 030, 222, 336) J. Postoperative median follow up was 22.9 (IQR 13.4, 41.7) months. Significant improvements were noted in IPSS, QoL scores, PVR, and Qmax after PVP treatment. At 12 months, the median decrease in IPSS, QoL scores, and PVR was 15 (IQR 14.5, 22) to 10 (IQR 5.5, 13.5), 5 (IQR 3.5, 5) to 2 (IQR 1, 3.5), 200 (IQR 171, 327.5) to 5 (IQR 1.25, 8), respectively (P < 0.05 for all). Similarly, at 12 months, the median increase in Qmax (ml/second) was 4 (IQR 3, 10) to 15.9 (IQR 11, 16) (P = 0.04). There were no reportable complications at 12 months. None of the 12 patients that underwent 532 nm GreenLight™ laser prostatectomy developed stress urinary incontinence. One patient developed metastatic prostate cancer and the remaining patients had no evidence of biochemical recurrence. Conclusion In this pilot study, 532 nm GreenLight™ laser prostatectomy is feasible and safe in patients who have undergone prior radiotherapy for prostate cancer. Laser prostatectomy provides a durable response while maintaining continence in this cohort suffering from severe lower urinary tract symptoms (LUTS) or retention. Larger, randomized trials comparing GreenLight™ laser prostatectomy to traditional TURP are necessary to confirm non‐inferiority. Lasers Surg. Med. 45:358–361, 2013. © 2013 Wiley Periodicals, Inc.